Angelwings You're never all alone - Donna Jo Napoli (United States, 2001)
"Why is everyone always so mean to Drew?" Drew is miserable. He and his family have just moved to a new house in Florida and Drew has no one to play with. His sisters are mean and bossy, and his parents are too busy unpacking to pay attention to him. The only one who wants to be around him is the crazy old dog across the street -- and Drew wants nothing to do with him. Can the Little Angel of Empathy help Drew get along with others -- or will he stay lonely forever?
Keywords: Fiction -- Fiction